MAGNETIC NANOPARTICLE SYNTHESIS AND APPLICATION: COMBINING BIOMEDICINE AND ENVIRONMENTAL USES - ULLAH, K; MEHBOOB, S; AHMAD, MW; AZIZ, S; NAZIR, Z; ALI, L; KOKAB, A (Biological and Clinical Sciences Research Journal, 2024)
Magnetic nanoparticles have attracted much attention in several industries, most notably medicine, due to their distinct magnetic characteristics and nanoscale size. They are perfect for many applications because they can precisely manipulate data. This study examines the methods used to create magnetic nanoparticles, specifically emphasizing chemical synthesis via reactions that occur in a solution. This approach enables precise control over the nanoparticles’ size, shape, structure, and magnetic characteristics. Recent research suggests that despite their promise, magnetic nanoparticles are inefficient for purifying water. Nevertheless, its use in the field of biomedicine, including medication administration, magnetic resonance imaging (MRI), and hyperthermia, is extensively scrutinized. Furthermore, this paper offers a summary of the use of magnetic nanoparticles in the fields of agriculture and wastewater treatment. The paper explores the creation and combination of magnesia materials for different life science uses, emphasizing the adaptability and importance of magnetic nanoparticles in contemporary scientific and industrial fields.